Sentinel-1 SAR Oceanography - Lehner, Susanne; Rosenthal, Wolfgang (2015)
With 90% of all goods being transported on sea routes an efficient, internationally competitive maritime industry is of high overall economic significance. The global exchange of goods is rising steadily causing an increase of ship traffic. New fuel efficient and safe routes are being discussed. In addition, tourism plays an increasingly important economic role at sea. To increase safety, security and efficiency of shipping and to protect the oceans, global data that provide reliable information about storms and sea state, sea ice cover, environmental pollution and ship and offshore locations are of paramount importance. This article demonstrates the use of Sentinel 1 data for wind field and sea-state information. The products are generated independently of weather conditions and in near-real-time and are delivered to operational users. High resolution measurements of wind and sea state fields are essential for maritime domain awareness are and frequently requested by shipping and offshore construction and maintenance. The usage of buoy data is restricted to local coverage and weather forecast systems can be improved by better quality of wind field input including frontal development and resolution of underwater topography. Using SAR data is a promising approach to integrate model and in situ data and their use provides the ability to monitor spacious ocean areas in all weather and sunlight illumination conditions. The derivation of wind and sea state parameters supports the planning and maintenance of offshore construction. Radar images and the value-adding products can be delivered to ship bridges and coordination centers within near real time, supporting Search and Rescue missions, Weather Services and pursuit of piracy, smuggling, illegal fishing and environmental crime. DLR developed a near-real-time processing chain for Sentinel ship detection, wind field and sea state derivation, oil spill and iceberg detection within the Payload Ground segment. The wind field and sea state products are delivered to ...